FMRFamide-Like Peptide 22 Influences the Head Movement, Host Finding, and Infection of Heterodera glycines - You, Jia; Pan, Fengjuan; Wang, Shuo; Wang, Yu; Hu, Yanfeng (Frontiers in Plant Science, 2021)
The FMRFamide-like peptides (FLPs) represent the largest family of nematode neuropeptides, and are involved in multiple parasitic activities. The immunoreactivity to FMRFamide within the nervous system of Heterodera glycines, the most economically damaging parasite of soybean [Glycine max L. (Merr)], has been reported in previous research. However, the family of genes encoding FLPs of H. glycines were not identified and functionally characterized. In this study, an FLP encoding gene Hg-flp-22 was cloned from H. glycines, and its functional characterization was uncovered by using in vitro RNA interference and application of synthetic peptides. Bioinformatics analysis showed that flp-22 is widely expressed in multiple nematode species, where they encode the highly conserved KWMRFamide motifs. qRT-PCR results revealed that Hg-flp-22 was highly expressed in the infective second-stage juveniles (J2s) and adult males. Silencing of Hg-flp-22 resulted in the reduced movement of J2s to host root, and penetration ability as well as their subsequent amount of females. Behavior and infection assays demonstrated that application of synthetic peptides Hg-FLP-22b (TPQGKWMRFa) and Hg-FLP-22c (KMAIEGGKWVRFa) significantly increased the head movement frequency and host invasion abilities in H. glycines but not in M. incognita. In addition, the number of H. glycines females on the host roots was found to be significantly higher in Hg-FLP-22b treated nematodes than the ddH2O-treated control J2s. These results presented here elucidated that Hg-flp-22 plays a role in regulating locomotion and infection of H. glycines. This suggests the potential of FLP signaling as putative control targets for H. glycines in soybean production.